2003
DOI: 10.1176/appi.ps.54.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Views of Causes of Aggression by Patients and Effective Interventions

Abstract: The participants indicated that both patients and staff play important parts in causing and in intervening to prevent violence. This information can be used to help plan programs to prevent and intervene in aggressive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Our previous work has shown an inverse relationship between the presence of regular nursing staff and violent incidents (Bowers, Allan, Simpson, Nijman, & Warren 2005a;Bowers, Nijman, Allan, Simpson, Warren, & Turner 2005c), as has that of others (Chou, Lu, & Mao 2002;Lanza et al 1994), and in surveys of staff or patients larger numbers are often seen as necessary to reduce levels of violence (FaganPryor et al 2003;Kumar, Guite, & Thornicroft 2001). However one other study has also reported a positive association between staffing numbers and patient aggression (Owen et al 1998).…”
Section: Discussionmentioning
confidence: 88%
“…Our previous work has shown an inverse relationship between the presence of regular nursing staff and violent incidents (Bowers, Allan, Simpson, Nijman, & Warren 2005a;Bowers, Nijman, Allan, Simpson, Warren, & Turner 2005c), as has that of others (Chou, Lu, & Mao 2002;Lanza et al 1994), and in surveys of staff or patients larger numbers are often seen as necessary to reduce levels of violence (FaganPryor et al 2003;Kumar, Guite, & Thornicroft 2001). However one other study has also reported a positive association between staffing numbers and patient aggression (Owen et al 1998).…”
Section: Discussionmentioning
confidence: 88%
“…People who were subjected to violence consider it difficult to discuss it in public, however, the management of an organization marred with acts of aggression finds it even harder to admit to it, fearing that it may possibly besmirch the organization's good name or methods of its management. Due to the growing number of cases of violence in the workplace, especially in scope of that of psychological nature, finding efficient ways of counteracting violence has become an urgent need [3,9,10]. The aim of this study was to estimate the level of exposure and average intensity of aggression towards particular professional groups of healthcare workers.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who had witnessed assaults by patients and were asked ''What causes patients to fight (or attack staff)?'' [5] cited both external (personal conflicts) and internal factors (cognitions, feelings, symptoms). Staff and patients report differing views of the reasons for aggressive incidents.…”
mentioning
confidence: 99%